Corporate Environmental Paradigms in Shift: Learning During the Course of Action at UPM–Kymmene - Halme, Minna (Journal of Management Studies, 2002)
Contrary to the popular conception in the corporate environmental management literature that corporations must learn new ecocentric paradigms before they can be expected to produce environmentally sound performance, the present results suggest that cognitive–level environmental learning in organizations does not inevitably precede behaviour change. Rather, at least partially, such learning is likely to occur in the course of action. The article also proposes that external pressure can set motion, but it alone does not lead to an environmental paradigm shift. In order to undergo such a shift, organizations will have to learn a meaning of their own to support new, more environmentally sound forms of activity.The present study examines empirically how two companies have learnt to incorporate environmental considerations into their managerial paradigms. It adopts a perspective according to which learning is portrayed as a process in which changes are brought about in the collective beliefs that the organization members hold about the relationship of their business to the natural environment (i.e. environmental management paradigm). Applying the grounded theory approach, the article identifies phases of environmental learning starting from the recognition or rejection of weak signals in ‘pockets’ of the organization, continuing through the gaining of new knowledge and experience towards ‘competition’ between old and new assumptions about the business–environment relationship, and finally proceeding to potential frame–break.